Method for removing haloacetic acid in water by using Fe-C nano material

By using Fe@C nanomaterials as catalysts and combined with electrochemical water treatment technology, the problems of high cost and poor catalytic performance of removing halogenated acetic acid in drinking water in the prior art are solved, and efficient and low-cost dehalogenation effect is achieved, and the water quality safety of drinking water is improved.

CN119774715AActive Publication Date: 2025-04-08ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411903477.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-08
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The prior art has problems such as high cost, harsh preparation conditions, poor catalytic performance and secondary pollution in removing halogenated acetic acid by-products in drinking water.

Method used

The targeted dehalogenation of halogenated organic acids is carried out through electrochemical water treatment technology using Fe@C nanomaterials as catalysts. Fe@C nanomaterials are closely combined with electrodes through magnetic properties, avoiding the defect of using binders in traditional methods.

Benefits of technology

It achieves efficient and low-cost dehalogenated acetic acid, reduces the content of disinfection by-products in drinking water, improves water quality safety, and avoids secondary pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774715A_ABST
    Figure CN119774715A_ABST
Patent Text Reader

Abstract

The invention discloses a method for removing haloacetic acid in water by using a Fe-C nano material. The method comprises the following steps: S1, obtaining a metal Fe organic framework material; s2, carbonizing the metal Fe organic framework material in a tubular furnace at the high temperature of 800 DEG C to obtain a Fe-C nano material; and S3, adding the Fe-coated C nano material into the water to be treated in the electrolytic tank device, and carrying out electrolytic dehalogenation on the haloacetic acid. The electrolytic tank device takes a steel electrode as a cathode and a graphite electrode as an anode or takes a Fe-coated C / magnetic electrode as the cathode and takes the graphite electrode as the anode. The Fe-coated C nano material and the Fe-coated C / modified magnetic electrode can be used for acid dechlorination of halogenated organic matters in electrochemical water treatment, and have the characteristics of targeted dehalogenation, high dehalogenation efficiency, low cost, simple preparation method, safety and stability, and the Fe-coated C / modified magnetic electrode abandons an adhesive in a nano material modified electrode method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of drinking water safety, and in particular relates to a method for removing halogenated disinfection byproducts of drinking water by electrocatalysis, and specifically relates to a method for removing halogenated acetic acid in water by using Fe@C nanomaterials. Background Art

[0002] Disinfection is an essential and critical step to ensure the safety of drinking water. The chlorine disinfection process has a history of hundreds of years and is still a widely used method for inactivating bacteria in drinking water worldwide. However, halogenated disinfection byproducts (X-DBPs) such as chloroform can be produced during the chlorine disinfection process. These X-DBPs have "three-hazard" effects and reduce the safety of drinking water quality.

[0003] Halogenated acetic acids (HAAs) are a class of disinfection byproducts with a high detection frequency and concentration in drinking water after trihalomethanes. Halogenated acetic acids have strong carcinogenicity and mutagenicity, and are also embryotoxic. They can cause damage to immune organs and pose a hazard to human health. Compared with volatile DBPs such as trihalomethanes and halogenated acetonitrile, halogenated acetic acids are not easy to volatilize, and the process of heating water in households has almost no removal effect on them. Therefore, it is of great significance to develop a convenient and efficient dehalogenation technology for halogenated disinfection byproducts to reduce and control DBPs in drinking water. Electrochemical technology is a method suitable for household terminal drinking water treatment. The cathode reduction reaction can break the C-Cl structure of halogenated organic matter to achieve targeted dehalogenation. In order to improve the dehalogenation effect, many studies are devoted to the development of new catalytic cathode materials, including precious metal-based catalysts, non-precious metal-based oxidants, carbon-based catalysts and organic-inorganic hybrids. However, these materials have the problems of high cost, harsh preparation conditions, poor catalytic performance and secondary pollution. Summary of the invention

[0004] In view of the problems existing in the prior art, the present application provides a method for removing halogenated acetic acid in water using Fe@C nanomaterials, with the goal of reducing the content of disinfection byproducts in drinking water. Based on the reduction reaction mechanism of halogenated organic matter dehalogenation degradation at the cathode, the present invention develops a magnetic catalytic nanomaterial Fe@C with enhanced electron transfer characteristics, which is used for electrochemical water treatment of halogenated organic matter acid dehalogenation. At the same time, a Fe@C / modified magnetic electrode material can also be prepared, which eliminates the adhesive in the nanomaterial modified electrode method and can also be used for electrochemical water treatment of halogenated organic matter acid dehalogenation. The dehalogenation method has the characteristics of targeted dehalogenation, high dehalogenation efficiency, low cost, simple preparation method, and safety and stability.

[0005] The technical solution adopted by the present invention is specifically as follows:

[0006] A method for removing halogenated acetic acid in water using Fe@C nanomaterials comprises the following steps:

[0007] S1. Obtaining metal Fe organic framework material;

[0008] S2, carbonizing the metal Fe organic framework material at 800° C. in a tube furnace to obtain Fe@C nanomaterial;

[0009] S3, adding Fe@C nanomaterials into the water to be treated in the electrolytic cell device to perform electrolytic dehalogenation of halogenated acetic acid.

[0010] Furthermore, in step S1, during the preparation of the metal Fe organic framework material, terephthalic acid and ferric chloride hexahydrate are used as precursors, which are added to a DMF solution and then the metal Fe organic framework material is prepared by a hydrothermal method.

[0011] Furthermore, the molar ratio of terephthalic acid, ferric chloride hexahydrate and DMF is 1:1:280, and the mixture is stirred at a medium temperature of 20-25°C for 2 hours to mix evenly; during the hydrothermal method, the metal Fe organic framework material is prepared by reacting in an oven at 150°C for 2 hours.

[0012] Furthermore, in step S2, during the high-temperature carbonization process, the heating rate is 5°C / min under nitrogen conditions, and the high-temperature reaction is 800°C in a tubular furnace.

[0013] Furthermore, in step S3, the electrolytic cell device uses a steel electrode as a cathode and a graphite electrode as an anode, and applies a current density of 10 to 50 mA / cm 2 , preferably 50 mA / cm 2 .

[0014] Further, in step S3, the electrolytic cell device uses the Fe@C / magnetic electrode as the cathode and the graphite electrode as the anode, and applies a current density of 10 to 50 mA / cm 2 , preferably 50 mA / cm 2 ; The method of adding the Fe@C nanomaterial is to modify the magnetic electrode to prepare the Fe@C / magnetic electrode material.

[0015] Furthermore, the magnetic electrode adopts a neodymium iron boron magnet.

[0016] Furthermore, in the process of preparing the Fe@C / modified magnetic electrode:

[0017] 1) preparing Fe@C nanomaterial dispersion;

[0018] 2) The magnetic electrode is polished with 600-1000 mesh sandpaper until there is no obvious dirt, then the aluminum oxide polishing liquid is applied to the surface and polished with the sandpaper until it is a bright mirror surface, and then rinsed with pure water; then it is ultrasonically cleaned and dried in anhydrous ethanol and pure water in turn; then the Fe@C nanomaterial dispersion is absorbed, dripped on the surface of the magnetic electrode and dried to obtain a Fe@C modified magnetic electrode; the preferred mass percentage of the aluminum oxide polishing liquid is 20%; the polished magnetic electrode surface is more susceptible to adsorption of Fe@C nanomaterials.

[0019] Furthermore, in step 1), during the process of preparing the Fe@C nanomaterial dispersion, the Fe@C nanomaterial is added into pure water and ultrasonically dispersed to obtain the Fe@C nanomaterial dispersion.

[0020] A Fe@C / modified magnetic electrode material, wherein the surface of the magnetic electrode is loaded with Fe@C material, and the loading amount is no more than 8 mg / cm 2 , preferably 6mg / cm 2 .

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention provides a method for reducing and dehalogenating halogenated organic matter by catalyzing it with Fe@C nanomaterials. The Fe@C nanomaterials used in the method have the characteristics of targeted dehalogenation, high dehalogenation efficiency, low cost, simple preparation method, and safety and stability.

[0023] 2. The present invention utilizes the magnetic characteristics of Fe@C nanomaterials, abandons the use of binders such as Nafion and polytetrafluoroethylene in traditional methods, and uses magnetic adsorption to achieve a close combination of catalytic materials and electrodes. During the electrochemical reaction, Fe@C nanomaterials do not fall off, and the material is adsorbed on the surface of the electrode, with a large contact interface with the aqueous solution, which greatly increases the catalytic incidence rate; the magnetic material after use can be easily and quickly recycled, replaced, and regenerated.

[0024] 3. The Fe@C nanomaterials obtained after carbonization are not only magnetic, but also have a larger specific surface area and good hydrophobicity, which increases the contact area of ​​the catalytic reaction.

[0025] 4. The preparation method of the Fe@C / modified magnetic electrode involved in the present invention is simple and low-cost, the material is green and environmentally friendly, and there is no secondary pollution; and it is suitable for the degradation of halogenated disinfection by-products in drinking water, reducing toxicity, and can further improve the safety of drinking water quality.

[0026] 5. Fe@C / modified magnetic electrodes can achieve efficient dehalogenation of halogenated disinfection by-products through electrocatalysis. Fe@C nanomaterials are used as catalysts to modify magnetic electrodes. During the electrolysis process, the electron transfer on the magnetic electrodes and the good catalytic activity of Fe@C nanomaterials form a reducing agent with dehalogenation ability, which can break the CX bond and dehalogenate the halogenated disinfection by-products. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The SEM images of the Fe@C nanomaterials of the present invention at different magnifications ((a) 10 μm, (b) 1 μm);

[0028] Figure 2 This is a comparison diagram of the effects of different dosing methods on trichloroacetic acid removal rates in the present invention;

[0029] Figure 3 This is a comparison diagram of the effects of different current densities on trichloroacetic acid removal rates in the present invention;

[0030] Figure 4 This is a comparison diagram of the effects of different Fe@C nanomaterial loadings on trichloroacetic acid removal rates of the present invention;

[0031] Figure 5 This is a comparison diagram of the effects of different pH values ​​on trichloroacetic acid removal rates according to the present invention;

[0032] Figure 6 This is a comparison diagram of the effects of different substrate concentrations on trichloroacetic acid removal rates of the present invention;

[0033] Figure 7 This is a schematic diagram of the electrocatalytic trichloroacetic acid dechlorination device of the present invention;

[0034] In the figure: 1. power box; 2. electrolyte; 3. electrode slot; 4. rotor; 5. beaker; 6. magnetic stirrer; 7. magnetic electrode. DETAILED DESCRIPTION

[0035] The various exemplary implementation cases of the present invention are described in detail below, and relevant diagrams are attached. This detailed description should not be considered as a limiting condition of the present invention, but should be considered as a detailed description of certain aspects and characteristics of the present invention. In addition, the numerical range in the present invention is only for judging the optimal range of the present invention, not for limiting the range, and values ​​outside this numerical range or other declarable values ​​are included in the present invention. In the case, unless otherwise specified, all equipment, reagents, techniques and scientific terms used are the same as those commonly understood and used by those skilled in the art in the field to which the present invention relates, and the instruments and reagents without indicating the manufacturer are also conventional products that can be purchased through general procurement channels.

[0036] Embodiment 1:

[0037] In the actual case, the target of electrocatalysis is trichloroacetic acid, and the initial concentrations of trichloroacetic acid are 100, 150, 200, 250 and 300 μg / L, respectively. The room temperature is 25°C. The magnetic electrode 7 in the embodiment is a NdFeB strong magnetic magnet with a specification of 50×50×2 mm. The ultrasonic frequency during the implementation process is 50 Hz.

[0038] This embodiment provides a method for preparing a Fe@C nanomaterial and treating trichloroacetic acid electrolytic de-brining water, which specifically comprises the following steps:

[0039] S1: 3mMFeCl3·6H2O, 3mM terephthalic acid and 65mLDMF were mixed and stirred for two hours, and then the obtained mixed solution was poured into the lining of the reactor, and the mixture was reacted at a constant temperature of 150°C in an oven for 15 hours; after the reaction, a reddish-brown product at the bottom was obtained by centrifugation, and the product was ultrasonically cleaned with DMF and anhydrous ethanol, respectively. Specifically, the reddish-brown product was added to the DMF solution, ultrasonically cleaned and centrifuged, and the upper DMF solution was poured out, and the operation was repeated twice; the reddish-brown product was added to the anhydrous ethanol solution, ultrasonically cleaned and centrifuged, and the upper anhydrous ethanol solution was poured out, and the operation was repeated twice, the centrifuge was centrifuged at 4000rpm for 10 minutes, the ultrasonic time was 30 minutes, and the DMF solution and the anhydrous ethanol solution were 50mL; finally, the product was dried in a vacuum oven at 60°C for 12 hours to obtain a metal Fe organic framework material.

[0040] S2: Carbonizing the prepared metal Fe organic framework material under nitrogen conditions to obtain Fe@C nanomaterials, wherein the heating rate is 5°C / min, and the reaction is carried out at a constant temperature of 800°C in a tube furnace for 2h. The scanning electron microscope image of the Fe@C nanomaterial is shown in Figure 1.

[0041] S3: Preparation of Fe@C nanomaterial dispersion: 200 mg of Fe@C nanomaterial was dispersed in 10.0 mL of pure water, and ultrasonicated at a frequency of 50 Hz for 30 min to obtain a 20 mg / mL Fe@C nanomaterial dispersion.

[0042] S4: Preparation of Fe@C / modified magnetic electrode. Grind the magnetic electrode with 800-mesh sandpaper, apply 20% by mass alumina polishing liquid on the surface and continue to polish until it is bright, then rinse with pure water; then place it in anhydrous ethanol, ultrasonicate for 20 minutes, then place it in pure water, ultrasonicate for 20 minutes, rinse with pure water, and dry naturally. Use a syringe to absorb the Fe@C nanomaterial dispersion, evenly drop it on the surface of the magnetic electrode, and dry it naturally to obtain a Fe@C / modified magnetic electrode. The loading amount of Fe@C nanomaterial on the modified electrode is 4 mg / cm 2 .

[0043] S5: Make an electrolytic cell device; the power box 1 provides power to the cathode and anode, a 2L beaker 5 is used as the electrolytic cell, a Fe@C / modified magnetic electrode is used as the cathode, a graphite electrode is used as the anode, the electrodes are fixed by the electrode slot 3, the spacing between the electrodes is 30mm, and the electrode slot 3 naturally sinks to the bottom of the cell. A rotor 4 is also placed at the bottom of the cell, and continuous stirring is achieved by a magnetic stirrer 6, with a rotation speed of 150rpm, so that the reaction in the electrolytic cell is uniform. The electrolytic cell is wrapped with tin foil to avoid light. The electrolytic cell device is as follows Figure 7 shown.

[0044] S6: Prepare 1L of electrolyte with initial concentrations of trichloroacetic acid of 100, 150, 200, 250 and 300 μg / L, adjust the solution pH to 7, and the current density to 50 mA / cm 2 . 30 mL samples were taken twice at 0, 1, 2, 4, 6 and 8 h after power-on to obtain two sets of parallel samples, and the concentration of trichloroacetic acid in the samples was determined by GC-ECD.

[0045] Using Fe@C nanomaterial modified electrode for electrocatalytic dechlorination, when the initial concentration of trichloroacetic acid was 300 μg / L, the removal rate of trichloroacetic acid was 84.0% after 8 hours of electrolysis. When the substrate concentration was 250, 200 and 150 μg / L, the removal rates of trichloroacetic acid were 87.6%, 96.0% and 97.3% after 8 hours of electrolysis. When the substrate concentration was 100 μg / L, the removal rate of trichloroacetic acid reached 98.1% after 8 hours of electrolysis. The change of trichloroacetic acid concentration conforms to the first-order reaction kinetics. The dechlorination effect of trichloroacetic acid with different initial concentrations over time is shown in Figure 2. Figure 6 shown.

[0046] Embodiment 2:

[0047] On the basis of Example 1, the dechlorination reaction of trichloroacetic acid by different dosing methods was studied, and the dosing methods were direct dosing without electrolysis (DCWE), direct dosing electrolysis (DCE), modified magnetic electrode electrolysis (MMEE), magnetic electrode electrolysis without dosing (MEWE) and steel electrode electrolysis without dosing (SEWE). Among them, DCWE is to directly add Fe@C nanomaterials to the trichloroacetic acid solution, and the electrolytic cell device is not powered; DCE is to directly add Fe@C nanomaterials to the trichloroacetic acid solution, and electrolysis is performed with a steel electrode as the cathode and a graphite electrode as the anode; MMEE is to perform electrolysis with Fe@C / modified magnetic electrode as the cathode and a graphite electrode as the anode; MEWE is to perform electrolysis with an unmodified magnetic electrode as the cathode and a graphite electrode as the anode; SEWE is to perform electrolysis with a steel electrode as the cathode and a graphite electrode as the anode. The initial concentration of trichloroacetic acid was 200 μg / L. Under the condition of 8 hours of electrolysis, the removal rates of trichloroacetic acid by DCWE, DCE, MMEE, MEWE and SEWE after 8 hours of electrolysis were 3.4%, 90.4%, 96.0%, 76.6% and 75.7%, respectively. The effect of different dosing methods on the removal rate of trichloroacetic acid is shown in the figure. Figure 2 shown.

[0048] Embodiment 3:

[0049] Based on Example 1, the effect of different current densities on the removal rate of trichloroacetic acid was investigated. The initial concentration of trichloroacetic acid was 200 μg / L, and the current densities were 10, 20, 30, 40 and 50 mA / cm 2 After 8 hours of electrolysis, the removal rates of trichloroacetic acid were 52.5%, 75.4%, 88.0%, 90.2% and 96.0% respectively; the removal effect increased with the increase of current density. The experimental results are shown in Figure 3 shown.

[0050] Embodiment 4:

[0051] On the basis of Example 1, the loading amount of Fe@C nanomaterials on the composite electrode was changed to 0, 2, 4, 6 and 8 mg / cm 2 , the initial concentration of trichloroacetic acid was 200 μg / L, and the current density was 50 mA / cm 2 , the solution pH is 7. Among them, when the loading amount is 6mg / cm 2 The removal rate can reach up to 97.5% when the specific load is 8 mg / cm 2 The removal rate was high (95.2%). The loadings were 0, 2 and 4 mg / cm 2 When , the removal rates were 85.0%, 93.2%, and 96.0%, respectively; the removal rates of electrolytic catalytic trichloroacetic acid degradation were Figure 4 .

[0052] Embodiment 5:

[0053] On the basis of Example 1, the pH in the electrolytic cell was changed to 11, 9, 7, 5 and 3, respectively, the initial concentration of trichloroacetic acid was 200 μg / L, the current density was 50 mA / cm 2 , the loading amount is 4mg / cm 2 The effect of different solution pH on electrolysis is as follows: Figure 5 As shown in the figure, the experimental results show that acidic conditions are more conducive to the electrolysis of the modified electrode. Acidic conditions will promote the generation of active H* and improve the catalytic reduction of trichloroacetic acid. At pH = 3, the removal rate can reach 96.9%. In the alkaline range of pH 9 to 11, trichloroacetic acid can still achieve a removal effect of more than 79.0%.

[0054] The Fe@C nanomaterial of the present invention can achieve a close connection between the modified layer and the cathode material by magnetic adsorption on the electrode material, and is convenient for recovery and regeneration. During the electrolysis process, the electron transfer on the magnetic electrode and the good catalytic activity of the Fe@C nanomaterial form a reducing agent with dehalogenation ability, which achieves the CX bond breaking, so that the halogenated disinfection byproducts are dehalogenated. The present invention uses trichloroacetic acid as a typical halogenated disinfection byproduct. The C-Cl bond is more difficult to break than the C-Br and CI bonds. The dechlorination effect of trichloroacetic acid can further illustrate the catalytic dehalogenation effect of the composite electrode. The composite electrode of the present invention is suitable for the degradation of halogenated disinfection byproducts in drinking water, and the toxicity is reduced, which can further improve the safety of drinking water quality.

[0055] The present invention has a current density of 50 mA / cm 2 , 200 μg / L trichloroacetic acid solution, solution volume 1L, solution pH 7, by adding MMEE, the loading amount of Fe@C nanomaterials on the modified electrode is 4 mg / cm 2 Under the condition of 8 hours of electrolysis, the dechlorination effect of trichloroacetic acid reached more than 96.0%, and the dechlorination efficiency was increased by 15% compared with the bare electrode.

[0056] The above is only the best specific implementation mode of the present invention, and the present invention is not limited thereto. Any technician who understands the field to which the present invention relates, any changes or substitutions that can be easily made within the technical scope provided by the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for removing halogenated acetic acid in water using Fe@C nanomaterials, characterized in that: The following steps are involved: S1. Obtaining metal Fe organic framework material; S2, carbonizing the metal Fe organic framework material at high temperature to obtain Fe@C nanomaterial; S3, adding Fe@C nanomaterials into the water to be treated in the electrolytic cell device to perform electrolytic dehalogenation of halogenated acetic acid.

2. The method for removing halogenated acetic acid in water according to claim 1, wherein In step S1, during the preparation of the metal Fe organic framework material, terephthalic acid and ferric chloride hexahydrate are used as precursors, which are added to a DMF solution and then the metal Fe organic framework material is prepared by a hydrothermal method.

3. The method for removing halogenated acetic acid in water according to claim 2, wherein: The molar ratio of terephthalic acid, ferric chloride hexahydrate and DMF solution is 1:1:280, and the mixture is stirred at a medium temperature of 20-25°C for 2 hours to mix well. During the hydrothermal preparation process, the mixture is reacted at 150°C for 2 hours.

4. The method for removing halogenated acetic acid in water according to claim 1, wherein In step S2, during the high-temperature carbonization process, the temperature is increased at a rate of 5°C / min under nitrogen conditions, and the reaction is carried out at 800°C in a tubular furnace.

5. The method for removing halogenated acetic acid in water according to claim 1, wherein In step S3, the electrolytic cell device uses a steel electrode as a cathode and a graphite electrode as an anode, and the current density is 10-50 mA / cm 2 .

6. The method for removing halogenated acetic acid in water according to claim 1, wherein In step S3, the electrolytic cell device uses Fe@C / magnetic electrode as cathode and graphite electrode as anode, and the current density is 10-50 mA / cm 2 ; The method of adding the Fe@C nanomaterial is to modify the magnetic electrode to prepare the Fe@C / magnetic electrode material.

7. The method for removing halogenated acetic acid in water according to claim 6, wherein: The magnetic electrode adopts a neodymium iron boron magnet.

8. The method for removing halogenated acetic acid in water according to claim 6, wherein: In the process of preparing the Fe@C / modified magnetic electrode: 1) preparing Fe@C nanomaterial dispersion; 2) The magnetic electrode is polished with 600-1000 mesh sandpaper until there is no obvious dirt, then the aluminum oxide polishing liquid is applied to the surface and the surface is polished with the sandpaper until it is a bright mirror surface, and then rinsed with pure water; then ultrasonically cleaned and dried in anhydrous ethanol and pure water in turn; then the Fe@C nanomaterial dispersion is absorbed, dripped on the surface of the magnetic electrode and dried to obtain a Fe@C / modified magnetic electrode.

9. The method for removing halogenated acetic acid in water according to claim 8, wherein: In step 1), during the process of preparing the Fe@C nanomaterial dispersion, the Fe@C nanomaterial is added into pure water and ultrasonically dispersed to obtain the Fe@C nanomaterial dispersion.

10. A Fe@C / modified magnetic electrode material, characterized in that: The surface of the magnetic electrode is loaded with Fe@C material, and the loading amount is no more than 8 mg / cm 2 .

Citation Information

Patent Citations

  • Dechlorination method and dechlorination device for chlorinated ethylene

    JP2016040036A

  • Robot safety evaluation method

    KR102759672B1